The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1159/000267044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Channel Blockers on Intraocular Pressure

Abstract: We determined the effects of either topical or systemic calcium channel antagonists on rabbit intraocular pressure (IOP). Topical nifedipine, verapamil or diltiazem had no significant effect on IOP. Intravenous verapamil and nifedipine caused statistically significant reductions in IOP between 2 and 6 h after administration; the nifedipine response followed an increase in IOP at 30 min. Diltiazem, given 3 times daily for 3 days, caused no pressure change. In the rabbit, therefore, calcium channel antagonists h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Previous reports have indicated that systemic administration of some Ca# + channel blockers either has no effect or causes a mild, but significant, reduction in IOP in conscious or anesthetized rabbits (Green and Kim, 1977 ;Beatty et al, 1984 ;Payne et al, 1990). In particular, Payne et al (1990) found that i.v. administration of verapamil or nifedipine caused a significant reduction in IOP between 2 and 6 hr after their administration in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that systemic administration of some Ca# + channel blockers either has no effect or causes a mild, but significant, reduction in IOP in conscious or anesthetized rabbits (Green and Kim, 1977 ;Beatty et al, 1984 ;Payne et al, 1990). In particular, Payne et al (1990) found that i.v. administration of verapamil or nifedipine caused a significant reduction in IOP between 2 and 6 hr after their administration in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, Segarra and colleagues have stated topical application of verapamil and nifedipine lowers IOP in conscious rabbits. 17 Another study demonstrates that calcium channel blockers in combination with antiglaucoma medications signifi cantly lower IOP in the primate eye.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these inhibitions may be partially reversed with verapamil [11]. Calcium channel blockers have widespread physiological and pharmacological actions [12][13][14]. In wound healing, calcium antagonists have been shown to inhibit platelet aggregation and activation, chemotaxis of polymorphonuclear leukocytes and fibroblast response [15][16][17].…”
Section: Discussionmentioning
confidence: 99%